2017
DOI: 10.7717/peerj.3412
|View full text |Cite
|
Sign up to set email alerts
|

Piwi1is essential for gametogenesis in molluskChlamys farreri

Abstract: Piwi (P-element induced wimpy testis) is an important gene involved in stem cell maintenance and gametogenesis in vertebrates. However, in most invertebrates, especially mollusks, the function of Piwi during gametogenesis remains largely unclear.To further understand the function of Piwi during gametogenesis, full-length cDNA of Piwi1 from scallop Chlamys farreri (Cf-Piwi1) was characterized, which consisted of a 2,637 bp open reading frame encoding an 878-amino acid protein. Cf-Piwi1 mRNA was mainly localized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Despite the likely more than seventy thousand living molluskan species 39 there exist only a few functional descriptions of PIWI proteins or piRNAs for this taxon based on experiments in the sea slug Aplysia californica 38 , the Farrer’s scallop Chlamys farreri 40 and in the dog whelk Nucella lapillus 41 . Importantly, Waldron et al 41 recently showed that piRNA-like small RNAs matching virus and transposon sequences are somatically expressed in Nucella lapillus .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the likely more than seventy thousand living molluskan species 39 there exist only a few functional descriptions of PIWI proteins or piRNAs for this taxon based on experiments in the sea slug Aplysia californica 38 , the Farrer’s scallop Chlamys farreri 40 and in the dog whelk Nucella lapillus 41 . Importantly, Waldron et al 41 recently showed that piRNA-like small RNAs matching virus and transposon sequences are somatically expressed in Nucella lapillus .…”
Section: Introductionmentioning
confidence: 99%
“…Different stages of sex cells were distinguished in the same acini of male gonads of L. grandis (spermatogonia, spermatocytes, spermatids and spermatozoa), as reported by Ma et al (2017) for the scallop Chlamys farreri (Johnes & Preston, 1904) and by Chatchavalvanich et al (2006) for the freshwater mussel Hyriopsis bialatus Simpson, 1900. This asynchronous gametogenesis in males of L. grandis occurs because different cohorts of gametes that are forming occur simultaneously, and this indicates that spermatozoa production is continuous during the development and maturity of the gonadal phases in males.…”
Section: 15mentioning
confidence: 64%
“…Mollusks are one of the largest groups of marine animals, of which Pinctada fucata is well studied due to its economic potential for pearl production and a model organism to investigate the fascinating biology of mollusks. Recent studies have revealed that PIWI proteins are ubiquitously expressed in mollusks (Rajasethupathy et al, 2012;Ma et al, 2017;Jehn et al, 2018). Moreover, abundant piRNA-sized small RNAs were observed in the oysters Crassostrea gigas (Xu et al, 2014;Zhou et al, 2014), Pinctada martensii (Jiao et al, 2014), and the scallop Chlamys farreri (Chen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%